Objects as Carriers of Engineering Knowledge. Issue 2 (4th May 2022) - Stacey, Martin; Eckert, Claudia
Abstract : The role of previous products in evolutionary engineering design is often neglected. In design discourse, references to objects provide terse expressions of complex information that cannot easily be expressed otherwise. Previous artifacts serve in conjunction with more general engineering knowledge to enable designers and design teams in engineering companies to work in ways that would be very difficult or impossible without them. They trigger the retrieval and active construction of personal knowledge, but also provide a scaffold for sharing knowledge and using it collectively. For companies, their products encapsulate and carry a significant part of the collective knowledge of the organization.